Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Tailoring MOF/PEO interface via self-assembled deep eutectic layer for advanced solid polymer electrolyte - Jing Li; Yifan Huang; Yaping Sun; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

Employment of magnetic measurements for monitoring conversion reactions in Fe3O4 anodes for lithium and sodium ion batteries - Bi Fu; Minghan Yang; Junfu Cheng; Zhanxu Chen; Yunbao Zheng; Yifang Li; Guangqi Hu; Yingji He; Chengzhi Hu; Yaping Wang (Chemical Engineering Journal, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Effective risks and dominant factors of drought-flood abrupt alternation events to global socio-ecological systems - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Baisha Weng; Jianzhu Li (Journal of Hydrology, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Loss of foxp3a drives sex-specific immune-metabolic remodeling across the gut-liver-gonad axis in zebrafish - Yuhang Hu; Deinyefa Godfree Igbiriki; Nan Wu; Jialin Li; Junheng Liu; Jiuwu Yin; Jinping Duan; Xianmei Li; Zhixian Qiao; Feng Xiong; Yingyin Cheng; Wanting Zhang; et al. (Fish & Shellfish Immunology, 2026)

A subset of cell cycle regulators co-expresses with cholesterol pathway and innate immune signaling during early GCRV infection in CIK cells - Waqar Younas; Lei Zhang; Mijuan Shi; Hong Yang; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Fish & Shellfish Immunology, 2026)

A Survey of the Species Origins of Common Fish Cell Lines—With a Particular Focus on the Grass Carp Ovarian Cell Line ( GCO ) - Hong Yang; Mijuan Shi; Yingyin Cheng; Wanting Zhang; Bin Gui; Rong Huang; Yaping Wang; Xiao‐Qin Xia (Journal of Fish Diseases, 2026)
Cell line misidentification or contamination undermines the reliability of research outcomes. In this study, we verified the species origin of commonly used fish cell lines, with a particular focus on the grass carp ovarian cell line (GCO). RNA‐seq data from 146 samples of 11 widely used fish cell lines were collected from public databases (NCBI‐SRA) and were mapped to the reference genomes of eight species. GCO RNA‐seq samples from three Chinese laboratories showed a mapping rate of 21.64% ± 3.61% to the grass carp genome, but 89.81% ± 4.83% to the fathead minnow genome. Further transcriptomic similarity analysis revealed that these GCO RNA‐seq samples clustered more closely with cell lines originating from fathead minnow. Targeted analysis of the COI gene amplification region confirmed that nearly all reads from GCO RNA‐seq samples mapped exclusively to the fathead minnow COI amplicon. Collectively, these results indicate that GCO may have undergone cross‐contamination or species misidentification. This study raises doubts about the true species origin of the GCO cell line and proposes that COI DNA barcoding can be used to discriminate the species origin of fish cell lines.

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

SETD2 Improves Endothelial Function and Angiogenesis in Diabetic Hindlimb Ischemia Via Activating ANGPT2-PI3K/AKT Pathway - Langtao Wang; Qing Wang; Jiaxing Duan; Yu Tan; Yuanyuan Liu; Shuai Hu; Cheng Wang; Chen Yang; Yanzhu Long; Jinxuan Wang; Tao Yu; Tianhu Liu; et al. (Cardiovascular Toxicology, 2026)

Natural anti-tobacco mosaic virus constituents from plants: A review - Junmei Wang; Juxiang Wang; Shanshan Xiao; Yingshun Miao; Zhengxuan Wang; Jueting Liu; Hongwei Wang; Yaping Liu; Hesham R. El-Seedi; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2026)

Linear time-lag effects and nonlinear interactions of global drought-flood abrupt alternation in responses to multiple factors - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Jianzhu Li (Journal of Hydrology, 2026)

Blueberry juice fermented by a high β-glucosidase-producing lactic acid bacterium mitigates skin aging by modulating gut microbiota - Shasha Cheng; Yaqi Liang; Yaping Zheng; Hongxuan Li; Yu Zhang; Yujun Jiang (Food Bioscience, 2026)

Trio-active bone scaffold with multivalent ion doping establishes an osteo–angio–immune bone regenerative axis - Jiren Yan; Xiang Li; Teng Ye; Weinan Cheng; Yaping Li; Gen Wen; Fei Zhang; Linyang Chu (Chemical Engineering Journal, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to ‘Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis’ [Aquaculture 578 (2024) 740142] - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2026)

Hydrogen bonding network induced by ambipolar small molecules facilitates high-performance all-solid-state Li batteries - Jing Li; Ruiqi Chai; Yaping Sun; Hengyi Wang; Cheng Lian; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Collaborative multi-CP model and meta-feedback learning-assisted matheuristic for solving the flexible job shop scheduling problem with sequence-dependent setup times - Weiyao Cheng; Chaoyong Zhang; Leilei Meng; Yaping Ren; Saif Ullah (Swarm and Evolutionary Computation, 2025)

Metabolic engineering of blueberry juice by Lactiplantibacillus plantarum JM065: Fermentation optimization - Shasha Cheng; Yaping Zheng; Hongxuan Li; Yujun Jiang; Yu Zhang (Food Chemistry, 2025)

A framework for the dynamic identification of drought propensity: The predictive role of energy changes in drought events - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng (Atmospheric Research, 2025)

Chemical composition and functional properties of protein-polyphenol complexes from purple rice: Effects of alkaline and enzymatic extraction - Yongchao Wang; Long Sun; Jianhong Peng; Zhengxuan Wang; Tianrui Zhao; Jianxin Cao; Yaping Liu; Guiguang Cheng; Charles Brennan (Food Chemistry, 2025)

Determination and Application of a New Drought Resistant Control Water Level for Multi-Reservoir Systems Based on a Water Resource Allocation Model - Yaping Cheng; Ziqi Yan; Denghua Yan; Miao Liu; Ruishen Wei (Water Resources Management, 2025)

Impact of wind and wave on the expansion of the Changjiang River plume in winter - Gaolei Cheng; Yaping Wang; Shaotian Li; Shiqiu Peng; Yuhang Zhu (Acta Oceanologica Sinica, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Unraveling the chrono-regulatory function of PhoP in nitrogen metabolism: A multi-scale engineering framework aimed at optimizing the synthesis of poly-γ-glutamic acid in Bacillus licheniformis - Qing Zhang; Shisi He; Zhihao Zhu; Fangzhou Cheng; Yaping Jin; Wanying Zhu; Fan Yang; Yaozhong Chen; Mengyuan Zhang; Xin Li; Dongbo Cai; Shouwen Chen (Chemical Engineering Journal, 2025)

Polysaccharide from discarded tobacco leaves and its anti-TMV activities - Yan Wang; Zhengxuan Wang; Yaping Liu; Charles Brennan; Jueting Liu; Jinhong Zhou; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2025)

Tyrosinase inhibition and enzyme kinetics of red rice bran protein peptides: Mechanism, identification, in silico exploration, and experimental validation - Zhenhao Zhao; Junbo Hu; Huimin Cui; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Bioscience, 2025)

Ghβ-LCY1 influences metabolism and photosynthetic in Gossypium hirsutum - Yanmin Qian; Yaping Wang; Yu Zhang; Zongyan Chu; Mengxin Shen; Cheng Zhang; Lihua Huang; Zhihua Yang; Kaiwen Ren; Yuanyuan Shi; Tingting Jiao; Baoting Yang; et al. (Plant Science, 2025)

Comparative analysis of Seabuckthorn and its significant component in enhancing fish mucosal immunity - Yuhang Liu; Lian Su; Danying Cao; Nan Wu; Yuhang Hu; Fatima Altaf; Jialin Li; Qingsong Zhu; Junheng Liu; Qianqian Zhang; Haokun Liu; Yingyin Cheng; et al. (Aquaculture, 2025)

The 2-aminoadipic acid (2-AAA) regulates grass carp ULK2 to inhibit GCRV replication - Xinyu Liang; Xuyang Wang; Xiaowen Zou; Qian Wang; Hanyue Wang; Cheng Yang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Libo He (Fish & Shellfish Immunology, 2025)

Gonadal expression profiles reveal the underlying mechanisms of temperature effects on sex determination in the large-scale loach (Paramisgurnus dabryanus) - Lei Zhang; Yutong Fang; Mijuan Shi; Keyi Ren; Xin Guan; Waqar Younas; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Animal Reproduction Science, 2025)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Multi-functional graphene aerogels/epoxy resin composites with Janus structure for enhanced electromagnetic interference shielding - Zhongjie He; Xiaoqian Li; Weirui Zhang; Xiaoyu Cheng; Mingzhong Wang; Wenjing Lu; Dongdong Yao; Yaping Zheng; Jiahe Liang (Chemical Engineering Journal, 2024)

The influences of extraction methods on the chemical constituents of Lyonia ovalifolia (wall.) Drude and intracellular protective effects based on metabolomics analysis - Chunyan Li; Mengcheng Li; Zhenhao Zhao; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Chemistry, 2024)

Angelica sinensis polysaccharides promote extramedullary stress erythropoiesis via ameliorating splenic glycolysis and EPO/STAT5 signaling-regulated macrophages - Nianci Sun; Ziling Wang; Honghui Jiang; Biyao Wang; Kunhang Du; Caihong Huang; Cheng Wang; Ting Yang; Yaping Wang; Yafei Liu; Lu Wang (Journal of Molecular Histology, 2024)

Latent heat type nanofluid based on MXene and MoS2 modified hierarchical structured phase change nanocapsules for sustainable and efficient light-heat conversion - Fangfang Su; Xiaoqian Li; Zhongjie He; Jinliang Xie; Weirui Zhang; Yangyang Xin; Xiaoyu Cheng; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2024)

Isolation and structural characterization of flavonoids from E Se tea and their synergistic inhibitory effects on lipid accumulation via regulating AMPK/ACC pathway - Jiaxiong Zhang; Jinke Zhang; Xiaoqian Wang; Taiming Chen; Zhengxuan Wang; Yaping Liu; Guiguang Cheng (Food Bioscience, 2024)

Phytochemicals from the rhizome of Bletilla formosana and their antioxidant, cytoprotective and anti-inflammatory activities - Yiqian Li; Luya Qiu; Yifen Wang; Zhengxuan Wang; Guiguang Cheng; Yaping Liu (Food Bioscience, 2024)

Well-cushioned and highly-elastic aerogel for multifunctional intelligent transportation packaging - Ruiming Liu; Xiaosen Pan; Zijun Mao; Zijun Xu; Yaping Zhu; Pan Xue; Zhengjian Zhang; Hongbin Liu; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2024)

Interactive effects of urine components and treatment conditions on antibiotic degradation of combined system integrating thermally activated peroxydisulfate and membrane distillation using machine learning - Yaping Lyu; Zifu Li; Zhiling Guo; Iseult Lynch; Peng Zhang; Shikun Cheng (Chemical Engineering Journal, 2024)

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Controlling release of astaxanthin in β-sitosterol oleogel-based emulsions via different self-assembled mechanisms and composition of the oleogelators - Shujie Wang; Yuyue Qin; Yaping Liu; Guoqin Liu; Guiguang Cheng; Thanapop Soteyome (Food Research International, 2024)

Unraveling the stereoscopic gene transcriptional landscape of zebrafish using FishSED, a fish spatial expression database with multispecies scalability - Cheng Guo; Weidong Ye; Danying Cao; Mijuan Shi; Wanting Zhang; Yingyin Cheng; Yaping Wang; Xiao-Qin Xia (Science China Life Sciences, 2024)

Grass carp peroxiredoxin 5 and 6-mediated autophagy inhibit grass carp reovirus replication and mitigate oxidative stress - Qian Wang; Xinyu Liang; Hanyue Wang; Cheng Yang; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Libo He (Fish & Shellfish Immunology, 2024)

Nanocellulose based ultra-elastic and durable foams for smart packaging applications - Yang Liu; Yaping Zhu; Zijun Xu; Xin Xu; Pan Xue; Hong Jiang; Zhengjian Zhang; Meng Gao; Hongbin Liu; Bowen Cheng (Carbohydrate Polymers, 2024)

Sinomenine improves resistance to foodborne enteritis and Anti-bacteria mucosal immunity in grass carp - Yuhang Liu; Danying Cao; Nan Wu; Xuyang Zhao; Qingsong Zhu; Lian Su; Fatima Altaf; Qianqian Zhang; Haokun Liu; Yongming Li; Bruno Hamish Unger; Yingyin Cheng; et al. (Aquaculture, 2024)

Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2024)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Apple trees can extract soil water from both deep layers and neighboring cropland in the tableland region of Chinese Loess Plateau - Yaping Wang; Xiaoyang Han; Weiming Yan; Liping Cheng; Xingdong Dang; Wenzhao Liu (CATENA, 2023)

Impact of the producer services agglomeration on PM2.5: A case study of the Yellow River Basin, China - Yan Liu; Yu Cheng; Ruijing Zheng; Huaxue Zhao; Yaping Wang (Journal of Geographical Sciences, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Protective effect of hot-water and ethanol-aqueous extracts from Anneslea fragrans against acetaminophen-induced acute liver injury in mice - Yiwen Hu; Mengcheng Li; Yongpeng Wang; Qingwang Xue; Xiaodong Luo; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Yudan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

How does digitalization drive carbon emissions? The inverted U-shaped effect in China - Ruijing Zheng; Ge Wu; Yu Cheng; Haimeng Liu; Yaping Wang; Xinyang Wang (Environmental Impact Assessment Review, 2023)

How can new-energy vehicle companies use organizational resilience to build business ecological advantages? The role of ecological niche and resource orchestration - Yaping Xie; Ruijun Chen; Jiru Cheng (Journal of Cleaner Production, 2023)

Influencing mechanism and hydrogeological implications of water level fluctuation of lakes in the northern Qaidam Basin, Qinghai-Tibet Plateau - Yaping Cheng; Qishun Fan; Tianyuan Chen; Haotian Yang; Qingkuan Li; Chunmei Han (Journal of Oceanology and Limnology, 2023)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Multi-response assessment for carbon emission and hardening effect in laser surface quenching - Jianzhao Wu; Chaoyong Zhang; Shuaikun Zhang; Yaping Ren; Hongwu Cheng; Guangdong Tian (Environmental Science and Pollution Research, 2023)

A molecular networking-based isolation of gardneria alkaloids from Gardneria distincta and their anti-inflammatory activity - Sifan Teng; Junjie He; Xiaoqian Wang; Yiqian Li; Afsar Khan; Tianrui Zhao; Yudan Wang; Guiguang Cheng; Yaping Liu (Phytochemistry, 2023)

Effect of ultra-high pressure pretreatment on the phenolic profiles, antioxidative activity and cytoprotective capacity of different phenolic fractions from Que Zui tea - Yongpeng Wang; Zhengxuan Wang; Qingwang Xue; Li Zhen; Yudan Wang; Jianxin Cao; Yaping Liu; Afsar Khan; Tianrui Zhao; Guiguang Cheng (Food Chemistry, 2023)

Protective effect of Anneslea fragrans ethanolic extract against CCl4-induced liver injury by inhibiting inflammatory response, oxidative stress and apoptosis - Yudan Wang; Xiaocui Deng; Yaping Liu; Yifen Wang; Xiaodong Luo; Tianrui Zhao; Zhengxuan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

New insights into membrane fouling during direct membrane filtration of municipal wastewater and fouling control with mechanical strategies - Yu Men; Zifu Li; Lixin Zhu; Xuemei Wang; Shikun Cheng; Yaping Lyu (Science of The Total Environment, 2023)

Simultaneous recovery of nutrients and water from human urine by a novel thermally activated peroxydisulfate and membrane distillation integrated system - Yaping Lyu; Xiuwei Ao; Shikun Cheng; Nana Liu; Yu Men; Zifu Li (Chemical Engineering Journal, 2023)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Changes in Microbial Diversity, Soil Function, and Plant Biomass of Cotton Rhizosphere Soil Under the Influence of Chlorpyrifos - Xiaobing Wang; Jian Wang; Yaping Wang; Xiaochong Zhu; Juan Cheng; Wei Wang (Current Microbiology, 2022)

Identifying the influencing factors and constructing incentive pattern of residents’ waste classification behavior using PCA-logistic regression - Ruijing Zheng; Mengqi Qiu; Yaping Wang; Deyang Zhang; Zeping Wang; Yu Cheng (Environmental Science and Pollution Research, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Impact of human capital on the green economy: empirical evidence from 30 Chinese provinces - Xinyang Wang; Yaping Wang; Ruijing Zheng; Jingjing Wang; Yu Cheng (Environmental Science and Pollution Research, 2022)

A New Dual-peak Fluorescent Probe for Water Content Detection Made From Taxus - Gang Wang; Yaping Li; Haipeng Chen; Shuqin Tang; Yiyang Cheng; Yuhong Yu; Abdul Qayoom Majeedano; Shangrao Pu; Gang Wang (Journal of Fluorescence, 2022)

Preferential removal of benzene, toluene, ethylbenzene, and xylene (BTEX) by persulfate in ethanol-containing aquifer materials - Huan Wang; Yudao Chen; Wei Meng; Yaping Jiang; Yaping Cheng (Environmental Science and Pollution Research, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Candidate gene analysis of watermelon stripe pattern locus ClSP ongoing recombination suppression - Zhen Yue; Rongxue Ma; Denghu Cheng; Xing Yan; Yaping He; Chunxia Wang; Xiaona Pan; Lijuan Yin; Xian Zhang; Chunhua Wei (Theoretical and Applied Genetics, 2021)

The inhibitory effects of the antifouling compound Irgarol 1051 on the marine diatom Skeletonema sp. across a broad range of photosynthetically active radiation - Yao Tang; Cheng Chen; Yangjie Sheng; Peijian Ding; Xinyu Wu; John Beardall; Yaping Wu (Environmental Science and Pollution Research, 2021)

The influence of VDR polymorphisms on the type 2 diabetes susceptibility in Chinese: an interaction with hypertriglyceridemia - Dongdong Zhang; Cheng Cheng; Yan Wang; Yuan Xue; Yaping Liu; Yiming Liu; Mingming Feng; Ze Xu; Wenjie Li; Xing Li (Molecular Genetics and Genomics, 2021)

A microcosm study on persulfate oxidation combined with enhanced bioremediation to remove dissolved BTEX in gasoline-contaminated groundwater - Yuan Xia; Yaping Cheng; Liuyue Li; Yudao Chen; Yaping Jiang (Biodegradation, 2020)

Cloud type identification for a landfalling typhoon based on millimeter-wave radar range-height-indicator data - Zhoujie Cheng; Ming Wei; Yaping Zhu; Jie Bai; Xiaoguang Sun; Li Gao (Frontiers of Earth Science, 2019)

Identification of Potential Biomarkers with Diagnostic Value in Pituitary Adenomas Using Prediction Analysis for Microarrays Method - Hu Peng; Yue Deng; Longhao Wang; Yin Cheng; Yaping Xu; Jianchun Liao; Hao Wu (Journal of Molecular Neuroscience, 2019)

Deep sequencing of small RNAs from 11 tissues of grass carp Ctenopharyngodon idella and discovery of sex‐related microRNAs - Liangming Chen; Rong Huang; Denghui Zhu; Cheng Yang; Libo He; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Journal of Fish Biology, 2019)
This research identified 169 known microRNAs (miRNAs), 380 novel miRNAs, and 30,538 targets in 11 tissues (blood, brain, derma, gill, heart, intestine, kidney, liver, muscle, pronephros, and spleen) from grass carp Ctenopharyngodon idella with high‐throughput sequencing (HTS). Transcripts per million (TPM) expression analysis detected 41 brain‐enriched miRNAs (accounting for 61.19% of all tissue‐enriched miRNAs). Real‐time quantitative PCR (RT‐qPCR) confirmed that 21 of 24 randomly selected tissue‐enriched miRNAs from the TPM analysis were indeed tissue‐enriched ( P dmrt ) involved in sex differentiation. RT‐qPCR revealed that cid‐miR ‐138 was more highly expressed in testis than in ovary ( P dmrt4a ( P cid‐miR ‐138– dmrt4a in neuroendocrine mechanisms related to brain‐pituitary networks during sex development. The discovery of miRNAs from 11 C. idella tissues expands the available fish mi R NA database, and enhances our understanding of the role of sex‐related miRNAs in tissue differentiation and maintenance of specific tissue functions in fishes.

Multi-Modality Cascaded Convolutional Neural Networks for Alzheimer’s Disease Diagnosis - Manhua Liu; Danni Cheng; Kundong Wang; Yaping Wang (Neuroinformatics, 2018)

Olfactory-ensheathing cells promote physiological repair of injured recurrent laryngeal nerves and functional recovery of glottises in dogs - Hongyi Liu; Yu Pu; Yaping Xu; He Xu; Huanhai Liu; Yin Cheng; Weihua Xu; Xiaoping Chen; Jingping Fan (Molecular and Cellular Biochemistry, 2018)

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L. - Lifei Luo; Rong Huang; Aidi Zhang; Cheng Yang; Liangming Chen; Denghui Zhu; Yongming Li; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang (Functional & Integrative Genomics, 2018)

Modeling the circulation and sediment transport in the Beibu Gulf - Gaolei Cheng; Wenping Gong; Yaping Wang; Zhen Xia (Acta Oceanologica Sinica, 2017)

Expression Profiles of SIRT1 and APP Genes in Human Neuroblastoma SK-N-SH Cells Treated with Two Epigenetic Agents - Yaping Hou; Fanghua Wang; Linping Cheng; Tao Luo; Jie Xu; Huaqiao Wang (Neuroscience Bulletin, 2016)

Flood-ebb asymmetry in current velocity and suspended sediment transport in the Changjiang Estuary - Zhanhai Li; Yaping Wang; Peng Cheng; Guoan Zhang; Jiufa Li (Acta Oceanologica Sinica, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The roles of endoplasmic reticulum stress response in female mammalian reproduction - Yanzhou Yang; Xiuying Pei; Yaping Jin; Yanrong Wang; Cheng Zhang (Cell and Tissue Research, 2016)

Kupffer-cell-expressed transmembrane TNF-α is a major contributor to lipopolysaccharide and D-galactosamine-induced liver injury - Peng Yang; Wenjing Zhou; Chenxi Li; Meng Zhang; Yaping Jiang; Rui Jiang; Hongping Ba; Cheng Li; Jing Wang; Bingjiao Yin; Feili Gong; Zhuoya Li (Cell and Tissue Research, 2016)

Efficient Knockout of Transplanted Green Fluorescent Protein Gene in Medaka Using TALENs - Chao Qiu; Bin Cheng; Yunsheng Zhang; Rong Huang; Lanjie Liao; Yongming Li; Daji Luo; Wei Hu; Yaping Wang (Marine Biotechnology, 2014)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Identification and expression profiles of prdm1 in medaka Oryzias latipes - Haobin Zhao; Xiaosha Zhang; Nana Cheng; Jundan Duan; Jialin Wang; Yoshitaka Nagahama; Xueping Zhong; Qingchun Zhou; Yaping Wang (Molecular Biology Reports, 2014)

Comparative proteomic and physiological analysis of diurnal changes in Nostoc flagelliforme - Wenyu Liang; Lingxia Wang; Yaping Zhang; Xiaoting Lei; Jia Yang; Xiangrong You; Chi-Lien Cheng; Youwen Zhou; Wei Chen (Journal of Applied Phycology, 2013)

Determination of Paracetamol Based on its Quenching Effect on the Photoluminescence of CdTe Fluorescence Probes - Li Li; Yaxiang Lu; Yaping Ding; Yu Cheng; Wanchen Xu; Fenfen Zhang (Journal of Fluorescence, 2012)

A diagnostic study of two heavy rainfall events in South China - Liji Wu; Yaping Shao; Andrew Y. S. Cheng (Meteorology and Atmospheric Physics, 2011)

Isolation and characterization of a rice mutant with narrow and rolled leaves - Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Shihua Cheng; Wenzhen Liu (Planta, 2010)